Stakeholder network integrated analysis: The specific case of rural tourism in the Portuguese Peneda-Gerês National Park - Nogueira, Sónia (2021)
This study addresses the structure, nature and composition of stakeholder networks related to rural tourism in a Portuguese National Park (Peneda-Gerês National Park). In particular, it examines their interactions along the following dimensions: marketing information (marketing exchanges such as flyers, tourism information and information on specific events), administrative resources (logistic and technical support), human resources (allocation of human resources), training (training of local stakeholders in the area of promotion) and financial resources (financial support). In terms of methodology, it uses both qualitative and quantitative techniques. The analysis of the type and nature of interactions among different stakeholders within a specific rural tourism destination is the main focus of this study. Among these, the marketing information network shows both a high number of connections and high centrality indices, which may indicate that there is a significant share of information about common projects, products and services among stakeholders. In contrast, the training network evidenced the opposite behavior pattern. The study also contributes to a better understanding of how different local stakeholders are positioned in a complex structure of interactions that are critical in providing useful directions to maximize potential opportunities that may contribute to promote rural tourism and local development efficiently. Several limitations and implications are offered in the final section.